Akibat Hukum Menikahi Wanita Hamil Sebab Zina - Ahmad Mustakim (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
Marrying a pregnant woman due to adultery is the marriage of a man with a woman who is already pregnant, either by being impregnated before marriage or impregnated by someone else before being married by a person who is not the father of the child. The legal basis for marrying a pregnant woman due to adultery can be found in Surah an-Nur:3. The law regarding marrying a pregnant woman due to adultery can be viewed from two perspectives: a) The man who marries is the adulterer's partner, and b) The man who marries is someone else. Scholars unanimously agree that a child born out of wedlock is considered a child of adultery if the man marrying the woman is not the one who impregnated her.